Comparing Thirty30 Tennis with Traditional Tennis - Peter O'Donoghue; Mark Milne (Universidad de Granada, 2020)
Thirty30 is a shorter format of tennis where games start at 30-30. This means that a greater proportion of points are game points or break points than would be the case in traditional tennis. The purpose of the current paper is to compare the probability of players of different abilities winning games, sets and matches between Thirty30 tennis and traditional tennis. This is done using probabilistic models of each format of tennis. The results show that there is reduced dominance of the serve and a greater probability of upsets in Thirty30 tennis than in traditional tennis. The models are also experimented with, adjusting the probability of winning points where the point is a game point or a break point. The paper shows that such scoreline effects have a greater impact in Thirty30 tennis than they do in traditional tennis. This has implications for player preparation for Thirty30 tennis.